Gibraltar : Detailed Assessment Report of Observance of the Insurance Core Principles. (IMF Staff Country Reports; Country Report, 2007)
This paper examines Gibraltar's Detailed Assessment Report of the Observance of the Insurance Core Principles. Foreign establishments operating in Gibraltar are all European Union (EU)-based and therefore covered by EU directives, including the directive on freedom of establishment. A key reason for the growth in this sector is the ability of firms licensed in Gibraltar to passport their services to EU member states. The domestic insurance market is, however, quite small with a population in the region of 30,000.